Fertility treatments in patients with medical conditions - Paramjit Uppal; Edward Coats; Charlotte Frise (Clinical Medicine)
The use of assisted reproductive technology (ART) has dramatically changed the landscape for treatment of infertility. Increasingly, healthcare practitioners of all specialisms are likely to encounter patients who have had ART, and therefore are expected to have knowledge of this area and counsel patients appropriately. There is, however, a lack of education about fertility techniques at both undergraduate and postgraduate level. Here we outline the main treatment options available to those undergoing ART, and the key considerations relevant to specialty physicians.